1999
DOI: 10.1037/0278-7393.25.3.721
|View full text |Cite
|
Sign up to set email alerts
|

Dual-coding, context-availability, and concreteness effects in sentence comprehension: An electrophysiological investigation.

Abstract: Event-related potentials were recorded in 2 experiments while participants read sentences in a word-byword congruency judgment task. Sentence final words were either congruent, semantically anomalous (Experiments 1 and 2), or neutral (Experiment 2) with respect to sentence context. Half of all final words referred to concrete and half to abstract concepts. A different scalp distribution of the N400 to concrete and abstract final words was found for anomalous and neutral, but not congruent sentences. Although t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

38
226
5
11

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(290 citation statements)
references
References 75 publications
38
226
5
11
Order By: Relevance
“…Although we carefully controlled our items for lexical properties such as length and class-specific word frequency, we did not control for all higher-level properties of the words (indeed, such control may not be possible). Concreteness, in particular, has been associated with effects that are in some ways similar to the pattern we observe in the present study, with more concrete words eliciting greater negativity (extending over frontal electrode sites) in the N400 time window (250-500 ms) and beyond (Kounios and Holcomb, 1994;Holcomb et al, 1999;West and Holcomb, 2000). This effect is most evident in imagery tasks and therefore has been interpreted as reflecting activation in a mental imagery subsystem, an information lookup system, or in working memory (West and Holcomb, 2000).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Although we carefully controlled our items for lexical properties such as length and class-specific word frequency, we did not control for all higher-level properties of the words (indeed, such control may not be possible). Concreteness, in particular, has been associated with effects that are in some ways similar to the pattern we observe in the present study, with more concrete words eliciting greater negativity (extending over frontal electrode sites) in the N400 time window (250-500 ms) and beyond (Kounios and Holcomb, 1994;Holcomb et al, 1999;West and Holcomb, 2000). This effect is most evident in imagery tasks and therefore has been interpreted as reflecting activation in a mental imagery subsystem, an information lookup system, or in working memory (West and Holcomb, 2000).…”
Section: Discussionsupporting
confidence: 84%
“…Most importantly, it is clear that concreteness cannot explain the whole pattern because a significant effect of semantic ambiguity could still be seen when a concretenessmatched subset (34 for AA and 64 for AU) of AA and AU items was compared [250-500 ms F(1,25) = 8.76; P < 0.01; 500-900 ms F(1,25) = 5.13; P < 0.05]. It is interesting to note that prior studies reporting ERP effects of concreteness did not control for word class or ambiguity and that at least some of the concrete words used in those studies (the full set of items was not reported) were actually both word class and semantically ambiguous (e.g., 'rose' in Holcomb et al, 1999). Thus, it is possible that the effect in those studies might have reflected the joint influence of concreteness and ambiguity; more work will be needed to disentangle these factors.…”
Section: Discussionmentioning
confidence: 92%
“…Holcomb and colleagues, in a series of event-related potential (ERP) studies (Holcomb, Kounios, Anderson, & West, 1999;Kounios & Holcomb, 1994;West & Holcomb, 2000), found that concrete words were associated with more negative-going potentials, beginning in the time window of the N400 component (~250-450 ms post-stimulus onset) and continuing to up to 800 ms. This concreteness-based difference was most pronounced over frontal scalp sites (whereas, in general, N400 effects have a centro-posterior focus).…”
Section: Introductionmentioning
confidence: 99%
“…The scalp distribution of the N400 found in sentence processing is influenced by the concreteness of the words. Concrete words, or words referring to pictureable objects, show a more anterior distribution than abstract words, which elicit a more centro-parietally distributed N400 [10]. Experiments looking at the semantic processing of anomalous pictures presented at a sentencefinal position report a frontally distributed N300 component and an anteriorly distributed N400 [7].…”
mentioning
confidence: 99%